2004
DOI: 10.1016/s0002-9440(10)63426-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Stathmin, a Microtubule-Destabilizing Protein, and Up-Regulation of Hsp25, Hsp27, and the Antioxidant Peroxiredoxin 6 in a Mouse Model of Familial Amyotrophic Lateral Sclerosis

Abstract: Gain-of-function mutations of the Cu/Zn superoxide dismutase (SOD1) gene cause dominantly inherited familial amyotrophic lateral sclerosis. The identification of differentially regulated proteins in spinal cords of paralyzed mice expressing SOD1(G93A) may contribute to understanding mechanisms of toxicity by mutant SOD1. Protein profiling showed dysregulation of Stathmin with a marked decrease of its most acidic and phosphorylated isoform, and up-regulation of heat shock proteins 25 and 27, peroxiredoxin 6, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 65 publications
12
74
1
Order By: Relevance
“…Spot 13 was increased up to 7-fold and identified as PDI, with 36% coverage by MALDI-TOF-MS. Spot 14 was characterized as Erp57, a second member of the PDI family, increased up to 6-fold, with 39% coverage by MALDI-TOF-MS analysis. A previous proteomic study did not identify the differential regulation of PDI family members (33). However, pooled tissue extracts were used that may mask identification of some proteins, and SOD1 G93A mice were used instead of rats.…”
Section: Pdi and Erp57 Are Significantly Up-regulated In Spinal Cordsmentioning
confidence: 99%
“…Spot 13 was increased up to 7-fold and identified as PDI, with 36% coverage by MALDI-TOF-MS. Spot 14 was characterized as Erp57, a second member of the PDI family, increased up to 6-fold, with 39% coverage by MALDI-TOF-MS analysis. A previous proteomic study did not identify the differential regulation of PDI family members (33). However, pooled tissue extracts were used that may mask identification of some proteins, and SOD1 G93A mice were used instead of rats.…”
Section: Pdi and Erp57 Are Significantly Up-regulated In Spinal Cordsmentioning
confidence: 99%
“…In the SOD1 mouse model of ALS, although there is a general increase in hsp27 and hsp70 levels in the spinal cord during disease progression, hsp27 is virtually absent from motoneuron cell bodies in symptomatic mice [5]. Similarly, it has also been shown that hsp25 immunoreactivity is present in motoneurons of presymptomatic but not symptomatic SOD1 mice [36]. In vitro, the combination of hsp40 and hsp70 overexpression has been shown to be protective against mutant SOD1-induced cell death [23].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances of neuronal transport have been suggested as potential causal factors in Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS) (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Data from cell cultures and preclinical models suggest that abnormal microtubule (MT) dynamics and MT-based neuronal transport may play a role (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%